Estudio del comportamiento del consumidor de productos químicos para la limpieza en la ciudad de Machala - Robles Romero, Andrea Cristina (2015)
Research in the city of Machala begins with the diagnosis under study, a research focused vision that seeks to achieve the necessary evidence strategizing customer profile. This market study finds that a large percentage of unmet demand for cleaning products, mainly in homes and there is a wide range of products we can offer to meet in a better way our prospects and also determining new niche markets such as companies like plus in our country new tariffs on imported products giving cavity in the market to domestic products were implemented. The buying habits of consumers are those who prefer to shop in supermarkets considering product quality as the first factor making purchases at an average of once a month and sometimes are motivated to certain seasonal promotions on the products. To achieve our objectives elaborate marketing strategies and implementation of flashy hangers inside the point of sale which will capture the customer's attention within the same they will have samples where guests can receive different types of fragrance product on offer, counting and the presence of a driving to hand information leaflets in which detailing the benefits, features use the same so you can encourage the purchase of the product also achieving greater positioning and brand development, according to all information obtained market this helps us determine consumer expectations when purchasing the product and thus find ways to make marketing campaigns that will ensure consumer satisfaction.